Theoretical analysis of [5.5.6]cyclacenes: electronic properties, strain energies and substituent effects. Issue 11 (20th February 2015) - Esser, Birgit
Abstract : [5.5.6] n Cyclacenes are proposed as low band gap, closed-shell materials and theoretically investigated regarding their structures, strain energies, aromaticity, electronic ground states, band gaps, and the effect of substituents. Abstract : A novel class of cyclic conjugated molecules, composed of annelated five- and six-membered rings, is proposed and theoretically investigated using density functional theory and multireference methods with regards to their structures, strain energies, aromaticity (NICS values), electronic ground states, band gaps, and the effect of substituents. These [5.5.6] n cyclacenes are predicted to be low band gap materials (below 1 eV) with, depending on their size, closed-shell singlet ground states. The strain energies from n = 4 upwards lie in the range of the synthetically known [ n ]cycloparaphenylenes. An investigation of the effect of rim-substitution by methyl, alkynyl, thiomethyl or phenyl groups on the electronic ground states showed that thiomethyl-substitution leads to [5.5.6] n cyclacenes with closed-shell singlet ground states for all sizes n investigated.